OPTIMISING THE USE OF MEDIA AND LEARNING TECHNOLOGY IN EDUCATION: A LITERATURE REVIEW OF FACTORS AFFECTING THE ADOPTION AND DIFFUSION OF INNOVATION IN IMPROVING THE EFFECTIVENESS OF THE TEACHING AND LEARNING PROCESS - Ismaul Fitroh; Rusiadi (CV. ADIBA AISHA AMIRA, 2025)
This study is a literature review that analyses the optimisation of the use of learning media and technology in educational settings through an understanding of the factors that influence the adoption and diffusion of innovation to improve the effectiveness of the teaching and learning process. Based on a review of Rogers' Diffusion of Innovations theory, the Technology Acceptance Model (TAM), and TPACK, it was found that the main factors include performance expectancy, effort expectancy, social influence, facilitating conditions, and obstacles such as infrastructure limitations and digital skills. Optimisation strategies include continuous teacher training, inclusive infrastructure development, blended learning, and national policies such as Merdeka Belajar (Freedom of Learning) that support pedagogical-technological integration. The results of the study show that a multifactorial holistic approach can accelerate the S-shaped adoption curve, increase student engagement, academic achievement, and personalisation of learning through data-driven evaluation. The practical implications provide recommendations for educators and policymakers to address the digital divide, while the theoretical implications enrich the framework of educational technology adoption in the Indonesian context. This study emphasises the need for evidence-based interventions for adaptive and inclusive 21st-century educational transformation.